Manajemen Krisis Public Relations Pinkflash: Dampak Pencabutan Izin Edar terhadap Citra Merek melalui Analisis Sentimen - Ulum Hidayah Suryani; Icha Ayu Anggita; Daffa Oktavianuri Ramadhan (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
The revocation of Pinkflash's cosmetic product distribution license by the Food and Drug Supervisory Agency (BPOM) has once again attracted public attention after the brand experienced a similar incident in 2024. This crisis raises questions about Pinkflash's public relations strategy in maintaining consumer trust and preserving its brand reputation. This study aims to analyze Pinkflash's public relations strategy and measure the impact of the crisis on public perception through social media sentiment analysis using Brand24. The research method used is a descriptive qualitative approach. The main data in this study was obtained from official documents by BPOM and official brand statements, which were then analyzed using content analysis and sentiment analysis using Brand24. The results of the study show that Pinkflash's crisis response only temporarily dampened negative sentiment. The root of the problem lies in weak governance, which led this study to conclude that reputation can only be rebuilt through comprehensive improvements to the quality of its systems and supply chain, with a commitment to honest operations as the key.